Karya Karawitan Inovatif “Dancing in The Storm” - I Gede Esa Supartha; Ni Ketut Dewi Yulianti; I Nyoman Mariyana (Journal of Music Science, Technology, and Industry, 2023)
Purpose: Human life has various kinds of unexpected things in it, just like lightning that can appear without waiting for rain to arrive. Lightning occurs because there is a potential difference between the cloud and the earth. The process of charge occurring in the cloud is due to its continuous, regular movement, and during that movement it will interact with other clouds so that negative charges will gather on one side, and positive charges on the other side. The purpose of creating this innovative karawitan work is to transform ideas that are born from natural phenomena, namely lightning, and to describe the values contained in the innovative karawitan work Dancing In The Storm. Method: The creation of the work "Dancing In The Storm" uses a method which consists of several elements in its creation, namely Composition, Creativity, and Exploration by Pande Made Sukerta. Composition is knowing the difference between timbre and sound quality. Results and discussion: Creativity (sening, feeling, imaging) exploration is an action to realize something you want. Karawitan's Innovative work dancing in the storm is an educational medium inspired by a natural phenomenon and someone's life story which, when combined, can become a correlation. Implication: In addition, there are also values contained in the Innovative Karawitan's Dancing In The Storm, namely story values (moral values) and formal values (artistic values).